Container Positivity and Larva Distribution Based on the Container Characteristics - Wanti Wanti; Ririh Yudhastuti; Subagyo Yotopranoto; Hari B. Notobroto; Sri Subekti; Sitti R. Umniati (International Journal of Public Health Science (IJPHS), 2017)
Dengue Haemorrhagic Fever (DHF) prevention and control program has been conducted in Kupang City but DHF Incidence Rate (IR) is always high and exceeds the national average. Calculating the density of larvae and pupae is a good choice in calculating DHF mosquitos’ density because larvae capture is easier than mosquitoes, and pupa is the nearest stage with adult mosquitoes so can better represent actual mosquito density. This observational study used cross sectional study design was conducted in Kupang City as many 24 urban villages or 480 houses during the rainy and dry season and all containers inside and outside homes selected been observed. Larvae and pupae were collected using gamadotik then identified. Analyzed data were using multiple regression logistic test, independent t test and Anova test. This study found 781 containers with the equation model of container positivity = 2,975 lid - 0.192 material + 0.781 type - 3,706, with the most influential variable is the container lid (OR 19.5). Ae. Aegypti, Ae. Albopictus and Culex can be found in water containers both inside and outside homes. The presence of larvae can be prevented either by doing closed and drain the container regularly and bury or drying container that is not used anymore. As limitation of water supply so other solutions need to be taken such as by sprinkling temefos into container with closed tightly to reduce the container positivity 19.5 times. For greater container can be done by water draining or reuse used container outside the home into a place to plant flowers or plants or become temporary garbage.